Nilai Nilai Eksistensi Tradisi Sekaten Dalam Perspektif Hukum Adat Dan Hukum Islam - Farizki Alam; Salsabella Vanisa Putri; Grace Oktavia; Anggita Yuniar; Anida Ayu Aminati (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research focuses on the values ​​of the existence of the sekaten tradition in the perspective of customary law and Islamic law, as stated in article 18B paragraph 2 which states that "The state recognizes and respects customary law community units and their traditional rights as long as they are still alive and in accordance with with the development of society and the principles of the Unitary State of the Republic of Indonesia." and also article 28 paragraph 3 which emphasizes that the cultural identity and rights of traditional communities must be respected along with developments over time. The method used in this research is Library Research, which means dissecting the value of the existence of the sekaten tradition and the formation of customary law and Islamic law. Customary law and Islamic law have become part of the positive legal system in Indonesia. In the formation of positive law in Indonesia, both customary law and Islamic law were recognized and integrated into the national legal framework. Islamic law encourages Muslims to create a just and harmonious society where individual interests do not outweigh social interests. These ideas are consistent with traditional beliefs that highlight the importance of community, solidarity, and mutual aid in society. However, it is important to realize that how Islamic law is interpreted and implemented varies across societies and countries.